Golden years? The labor market effects of caring for grandchildren - Ying Wang; Dave E. Marcotte (Institute for the Study of Labor (IZA), 2007)
The number of Americans raising grandchildren has been rising steadily. In this paper, we add to what is known about the implications of this trend by focusing on the economic effects of raising a grandchild. We make use of a unique data set compiled from the Panel Study of Income Dynamics along with its Parent Identification File. Using this nationally representative sample of 3,240 grandparents who are heads of households, we estimate the effect of taking in a grandchild on a grandparent's labor force participation and hours worked. We estimate ordinary and two-stage models that distinguishing between grandparents living only with grandchildren (skipped generation families) and those who also have taken in their own children (three-generation families). The results suggest that caring for grandchildren leads to greater attachment to the labor force, especially in skipped-generation families, for grandfathers, and among married grandparents
urn:nbn:de:101:1-20080416354
Keywords: 330; Kinderbetreuung; Alte Menschen; Arbeitsangebot; Altersgrenze; USA